English Day Program Implementation In The Students’ Speaking Skill Of SMAN 2 Luwu - Maritu, Juwita Crestiani; Indah, Opik Dwi; Hermini, Hermini (Pustaka Digital Indonesia, 2024)
This research deals with the English Day Program Implementation in the students’ Speaking Skill at the Twelfth Grade of SMAN 2 Luwu. The researcher applied the random sampling technique from each class. There were 10 students as sample to be given questionnaire. The instrument of this research is questionnaire comprise list of questions. Based on the findings and discussion in the previous chapter, the researcher concludes the English Day Program implementation is appropriate in the students’ Speaking Skill because the student enjoy during learning process so the student can understand material easier. Besides that, does not make students get bored, confident in speaking English without afraid of making mistake. It’s shows that all students give positive respond toward English Day Program implementation is appropriate in the students’ Speaking Skill.